Usos e dilemas da maconha/cannabis no Brasil: entre o desvio e a norma - Lustosa, Raissa Soares (2019)
This paper is a qualitative research of sociological nature, which aims to analyze the contemporary Brazilian scenario regarding the use of marijuana/cannabis and the dilemmas that permeate the implementation of a new legal normative posture in relation to the plant. To this end, an empirical research with field research was conducted in an association that grows and produces cannabis oils and extracts - Abrace Esperança - and semi-structured interviews with the employees of this association and with parents and caregivers of medicinal cannabis users. In light of the theoretical framework of the Sociology of Drugs and Deviance and key concepts such as norm, deviance, stigma and morality, we have identified that marijuana/cannabis is moving towards a context of social, political, moral and normative (re) meaning that it intends to the debate over the regulation of this “plant/drug/medicine” in Brazil. The main conclusion of the data analysis is that the revival of marijuana/cannabis as a medicine has given rise to a new 'cycle of attention' to the plant, integrating new social actors, discourses, practices and meanings around use marijuana/cannabis, which demand changes in the rules that regulate the use, production and control of the plant in the country. This new plant paradigm has raised issues such as recognition of the practice of traditional plant uses, the semantic dispute over terms surrounding the plant and its uses: cannabis/marijuana and recreational use/social use, the place of cannabis herbal medicine in orientation of the medicinal use of the active principles of the plant, the adoption of the medical referential as a privileged form of state policy. Finally, the results highlight the importance of the protagonist role of the association Abrace Esperança and of the mothers regarding the advances and regulatory milestones in public policies and in the legal field involving the plant and its uses.